Revisiting the lithic industries of El Abra sites (Sabana de Bogotá, Colombia, Northern South America). Implications for its significance and chronology. (20th March 2021) - Muttillo, Brunella; Lleras Pérez, Roberto; Rufo, Ettore; Lembo, Giuseppe
Abstract: In this paper we present a revision of the lithic industries of El Abra sites (Sabana de Bogotá, Eastern Cordillera, Colombia), among the most ancient and significant sites of Colombia. Dated to 12, 400 ± 160 years BP, El Abra is an important reference for the prehistory of the country. Our review mostly deals with the: a) methodological approach adopted for the study of the lithic industry; b) interpretation of the lithic industry; c) chrono-stratigraphy. In 2017, 2019 we presented the revision of the lithic assemblages of the oldest levels of El Abra sites (Muttillo et al., 2019, 2017); here we integrate and complete the revision with the analysis of the lithic assemblages of the upper levels. This is the first revision of the historical lithic collections, adopting a technological approach and crossing the data with the chrono-stratigraphic context. Our results have highlighted several discrepancies and critical elements contained in previous studies, that mostly affect not only the interpretation of the lithic industries but also the chronology of the site, that turned out to be more recent than previously assumed, for at least three thousand years.